2011
DOI: 10.3109/15622975.2011.582883
|View full text |Cite
|
Sign up to set email alerts
|

The association between brain-derived neurotrophic factor Val66Met variants and psychotic symptoms in posttraumatic stress disorder

Abstract: Objectives. Psychotic symptoms frequently occur in veterans with combat-related posttraumatic stress disorder (PTSD). Brain-derived neurotrophic factor (BDNF) plays a major role in neurodevelopment, neuro-regeneration, neurotransmission, learning, regulation of mood and stress responses. The Met allele of the functional polymorphism, BDNF Val66Met, is associated with psychotic disorders. This study intended to assess whether the Met allele is overrepresented in unrelated Caucasian male veterans with psychotic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
56
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(61 citation statements)
references
References 23 publications
4
56
0
Order By: Relevance
“…However, the Met allele (one and two alleles) of BDNF Val66Met polymorphism may be associated with PTSD severity in veterans (Pivac et al. 2012). …”
Section: Introductionmentioning
confidence: 99%
“…However, the Met allele (one and two alleles) of BDNF Val66Met polymorphism may be associated with PTSD severity in veterans (Pivac et al. 2012). …”
Section: Introductionmentioning
confidence: 99%
“…The related studies were conducted in adults among European (Croatia), Asian (South Korea) and American populations (USA and Brazil). In detail, 3 articles [16,19,26] involved healthy individuals as controls, and another 2 papers [14,17] used people who suffered from the same stress as cases but without PTSD symptoms - 1 article [18 ]contained both types of controls and thus were treated separately as 2 studies. In addition, 2 articles [14,17] examined PTSD participants who were exposed to stress/traumatic events from active duty in the army.…”
Section: Resultsmentioning
confidence: 99%
“…During each stage of screening, the literature articles were clearly identified and a consensus could be established. Finally, 6 articles [14,16,17,18,19,26] were selected. Articles in each selection step are shown in online supplementary figure S1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The main results of these studies show that subjects with PTSD-SP have 1) a higher concentration of platelet serotonin, 2) higher levels of corticotropin-releasing factor in the cerebros pinal fluid, 3) a higher concentration of plasma dopamine beta-hydroxylase, 4) specific deficits in smooth pursuit eye movement, and 5) a higher presence of Met alleles in the BDNF Val66Met polymorphism [94][95][96][97][98] . Likewise, different open clinical trials found that the administration of neuroleptics as a monotherapy for 6-8 weeks reduces symptoms in those subjects with PTSD-SP resistant to conventional antidepressant treatment [99][100][101] .…”
Section: -Nosological Status Of Ptsd-spmentioning
confidence: 99%